Concept, Design, Initial Tests and Prototype of Customized Upper Limb Prosthesis - Corina Radu (Frenț); Maria Magdalena Roșu; Lucian Matei; Liviu Marian Ungureanu; Mihaiela Iliescu (Applied Sciences, 2021)
This paper presents aspects of the concept and design of prostheses for the upper limb. The objective of this research is that of prototyping a customized prosthesis, with EMG signals that initiate the motion. The prosthesis’ fingers’ motions (as well as that of its hand and forearm parts) are driven by micro-motors, and assisted by the individualized command and control system. The software and hardware tandem concept of this mechatronic system enables complex motion (in the horizontal and vertical plane) with accurate trajectory and different set rules (gripping pressure, object temperature, acceleration towards the object). One important idea is regarding customization via reverse engineering techniques. Due to this, the dimensions and appearance (geometric characteristics) of the prosthesis would look like the human hand itself. The trajectories and motions of the fingers, thumbs, and joints have been studied by kinematic analysis with the matrix–vector method aided by Matlab. The concept and design of the mechanical parts allow for complex finger motion—rotational motion in two planes. The command and control system is embedded, and data received from the sensors are processed by a micro-controller for managing micro-motor control. Preliminary testing of the sensors and micro-motors on a small platform, Arduino, was performed. Prototyping of the mechanical components has been a challenge because of the high accuracy needed for the geometric precision of the parts. Several techniques of rapid prototyping were considered, but only DLP (digital light processing) proved to be the right one.